(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Selective alkylation of 5-(p-aminophenyl)-1,3,4-oxadiazol-2(3H)-thione with alkyl halides have been studied. It was revealed that alkylation goes on more polarized thiogroup in position 2 and corresponding 2-alkylthio-1,3,4-oxadiazoles were obtained in high yields. Structure of novel synthesized compounds confirmed by physical methods of research as UV-, IR- and 1H NMR-spectroscopy. Primary in vitro biological activity have been studied and it was found that all obtained S-alkyl derivatives have weak activity against bacteria Xanthomonas malvacearum and fungicidal activity against fungi Fusarium oxysporum.